Reactive Oxygen Species Enhance TLR10 Expression in the Human Monocytic Cell Line THP-1 - Kim, Donghee; Kim, Yeon Ju; Koh, Hyun Sook; Jang, Tae Yang; Park, Hyo Eun; Kim, Jae Young (International journal of molecular sciences, 2010)
We investigated TLR10 expression in human monocytes, THP-1 cells, cultured in hypoxia (3% O2). Levels of both TLR10 mRNA and protein in THP-1 cells cultured in hypoxia were significantly higher than those cultured in normoxia (20% O2). We examined intracellular reactive oxygen species (ROS) content in hypoxic cells, and TLR10 expression in cells treated with hydrogen peroxide (H2O2), to determine whether the increase in TLR10 expression observed with hypoxia was due to an increase in intracellular ROS levels. We found that the level of intracellular ROS in cells subject to hypoxia was significantly higher than in normoxia. Experiments with ROS synthesis inhibitors revealed that hypoxia induced ROS production is mainly due to NADPH oxidase activity. TLR10 mRNA expression was increased by treatment with H2O2 at concentrations ranging from 50 to 250 μM. We screened the TLR10 promoter and found putative binding sites for transcription factors (TFs), such as NF-κB, NF-AT and AP-1. Next, we examined TF activities using a luciferase reporter assay. Activities of NF-κB, NF-AT and AP-1 in the cells treated with H2O2 were significantly higher than in untreated cells. The experiment with TF inhibitors revealed that ROS-induced upregulation of TLR10 expression is mainly due to NF-κB activation. Overall, our results suggest that hypoxia or ROS increase TLR10 expression in human monocytes and the transcriptional activities of NF-κB are involved in this process. Therefore, it is suggested that ROS produced by various exogenous stimuli may play a crucial role in the regulation of expression and function of TLR10 as second messengers.